Incidence of intra and postoperative complications associated with transesophageal echocardiograms (TEE) in pediatric patients - Hall, Michael (2016)
The benefits of intraoperative transesophageal echocardiography (TEE) during cardiac surgery are well documented. Intraoperative TEE accurately confirms and in many cases refines delineation of congenital heart lesions, can be used as a means for establishing an intraoperative technical surgical score, and offers a low incidence of intraoperative complications. It seemed likely that the rate of perioperative complications in children would be congruent with the current available data in adults. After Institutional Review Board approval, a retrospective chart review of patients at Boston Children's Hospital who underwent the TEE procedure between May 2012 and December 2014 was conducted. The final study sample consisted of 129 patient charts. Adverse events related to TEE were documented and defined as follows: 1) those potentially attributable to TEE and 2) those with a high likelihood of being related to TEE; defined as dysphagia, esophageal perforation, gastrointestinal bleeding, and throat discomfort/pain. Of the 129 total cases, there was only one case reporting an intraoperative adverse event with a high likelihood of being related to TEE. This incidence rate of 0.77% is consistent with the literature existing on adult and pediatric TEE safety studies. Literature on postoperative adverse events related to intraoperative TEE use in pediatric patients was limited to the incidence of dysphagia. The sample included no incidence of dysphagia and the review enumerated six postoperative adverse events (4.65%) of which had a high likelihood of being related to TEE. Three of these events were classified as major and three were classified as minor. Major postoperative events included blood draining from nasogastric/orogastric tubes and blood tinged secretions suctioned from the endotracheal tube. Minor events were patient reported as sore throat and voice hoarseness. It was concluded that TEE use is not associated with an increased risk of adverse events in pediatric patients if performed according to institutional procedure and recommendations. Intraoperative TEE offers immediate assessment of the adequacy of surgical repair and presence of residual lesions. This information can be used to generate a surgical technical performance score. The ability to detect and correct residual lesions with information provided by intraoperative TEE allows the surgeon to improve technical performance thereby reducing postoperative morbidity.